2003
DOI: 10.1038/sj.ijir.3900985
|View full text |Cite
|
Sign up to set email alerts
|

Vardenafil enhances clitoral and vaginal blood flow responses to pelvic nerve stimulation in female dogs

Abstract: The relaxation of the smooth muscle in the vagina and clitoris and the increase of blood flow into these organs is thought to be essential in the female sexual response. Vardenafil is a type 5 phosphodiesterase (PDE5) inhibitor that potentiates the nitric oxide (NO)/cGMP pathway facilitating penile smooth muscle relaxation and improving penile erection in men. Although the potentiation of the NO/cGMP pathway through PDE5 inhibitors can clearly enhance blood flow into the penis and is used in the therapy of mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 29 publications
4
26
0
Order By: Relevance
“…The role of NO in neurogenic relaxation and blood flow control in the clitoris and vagina is supported by substantial evidence (Cellek and Moncada, 1998;Ziessen et al, 2002;Angulo et al, 2003). Our study provides further support for a key role of the NO/cGMP pathway in GVRs since the inhibition of NOS greatly inhibits GVRs to PNES.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The role of NO in neurogenic relaxation and blood flow control in the clitoris and vagina is supported by substantial evidence (Cellek and Moncada, 1998;Ziessen et al, 2002;Angulo et al, 2003). Our study provides further support for a key role of the NO/cGMP pathway in GVRs since the inhibition of NOS greatly inhibits GVRs to PNES.…”
Section: Discussionsupporting
confidence: 62%
“…Nitrergic innervation has also been identified in the human vagina and clitoris (Hoyle et al, 1996;Burnett et al, 1997). We have recently shown that the enhancement of the NO/cGMP pathway by the inhibition of type 5 phosphodiesterase potentiates increases in vaginal and clitoral blood flow in response to pelvic nerve electrical stimulation (PNES) in female dogs (Angulo et al, 2003). On the other hand, it has been suggested that the adrenergic system could play a functional antagonistic role to the NO pathway in female sexual responses (Giuliano et al, 2001), as occurs in males.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The stimulation of the paravertebral sympathetic chain reverses the PNS‐induced effect in the rat [32]. In both the rabbit and the dog model, the PDE5 inhibitors sildenafil and vardenafil, respectively, enhanced the PNS‐induced vaginal and clitoral blood flow indicating that the NO/cGMP pathway is involved in the physiological mechanism of female genital arousal [58,61]. The role of the NO/cGMP system in clitoral erection is further indicated by in vitro animal experiments.…”
Section: Animal Studiesmentioning
confidence: 99%
“…PDE-5 inhibitors enhance pelvic nerve-stimulated blood flow (e.g., sildenafil, [1]; vardenafil, [23]) although the effects of zaprinast in this model system have yet to be evaluated. Our working model is that the enhanced genital blood flow elicited by zaprinast leads to heightened vaginal sensitivity to mating stimulation manifested behaviorally as a lengthening of contact-return latencies following ejaculation, as exhibited in the present study.…”
Section: Discussionmentioning
confidence: 99%